Prospects of Agribusiness as Supporting Food Security in the Semarang City - Dhani, Ali Umar; Apriyanti, Hani Werdi (Faculty of Economics and Business UNTAG Semarang, 2022)
This study aims to elaborate on the potential of urban agricultural agribusiness in Semarang City and identify development sectors that can receive/provide co-benefits from urban agricultural development. The research method used is mixed, with primary and secondary data obtained and analyzed using quantitative and qualitative descriptive methods. The results of the study indicate that there is potential for agribusiness in Semarang City to support national food security. Agribusiness development can be carried out in accordance with the national agricultural development master plan, in order of priority, in accordance with the mapping of potential in the city of Semarang, and guided by the medium-term and long-term development plans of the city of Semarang.